Experimental Study on the Application of a Local Propeller for Improving the Propulsion Performance of FRP Fishing Vessels - Nanang Setiyobudi; Oktavian Rahardjo; Ari B. Setiawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This study aims to evaluate the performance improvement of fishing vessels made of fiberglass-reinforced plastic (FRP) using locally manufactured propulsion components. Two vessels, KM. Nelayan 271 and KM. Nelayan 371, were tested to identify and resolve the underperformance issue, as both initially failed to achieve the target service speed of 7 knots. The experimental approach involved field installation, configuration adjustment, and sea trials. On KM. Nelayan 271 , the original D22×P20 (three-blade) propeller was replaced with a D24×P22 (four-blade) model, resulting in a speed increase from 5.3 to approximately 7.1 knots at 2000 RPM. On KM. Nelayan 371, the gearbox was replaced from WHG17G (3:1) to MA125 (2:1), allowing the vessel to exceed 8.3 knots using the same propeller configuration. These results demonstrate that optimizing the gearbox ratio and propeller geometry effectively restores the propulsion balance and enhances vessel performance. The findings provide empirical validation that domestically manufactured components, specifically the B-Series propellers produced by BTH Surabaya, can meet the operational standards for small fishing vessels. This achievement supports Indonesia’s initiative to strengthen the TKDN policy and reduce reliance on imported marine propulsion systems.